2013
DOI: 10.3390/chemosensors2010001
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Properties of Hydrogels Containing Phenylboronic Acids

Abstract: Phenylboronic acids are a class of compounds that bind glucose and other sugars. When polymerized into hydrogels, they provide a convenient nonenzymatic means for sensing glucose concentration, provided competing sugars are present at negligible concentrations. In this paper we provide a comprehensive study of swelling of hydrogels containing methacrylamidophenylboronic acid (MPBA), as a function of pH and concentration of either glucose or fructose. In one set of hydrogels, MPBA is substituted at 20 mol· % in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 35 publications
(56 reference statements)
3
33
0
1
Order By: Relevance
“…Here, it can be revealed that the binding of glucose moieties with the mineralized hydrogels gradually increases the charge density within the hydrogels, hence enhances the hydrophilicity within the hydrogel which finally leads to the rise in the swelling capacity (Kim et al 2014). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it can be revealed that the binding of glucose moieties with the mineralized hydrogels gradually increases the charge density within the hydrogels, hence enhances the hydrophilicity within the hydrogel which finally leads to the rise in the swelling capacity (Kim et al 2014). …”
Section: Resultsmentioning
confidence: 99%
“…As far as the swelling behavior is concerned, two main important phenomenons are focused: (1) Donnan osmotic pressure and (2) elastic property within the polymeric network structure. When these two phenomena become equal, no further uptake of the solution takes place by the material and hence super-saturation stage is attained (Kim et al 2014).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Thus PBA is an excellent Lewis acid, which complexes with Lewis bases such as:OH − and –N: groups. The most commonly studied PBA, methacrylamidophenylboronic acid (MPBA) acts, when in a hydrogel, as an acid with pKa≈8.5 [150, 151]. At physiologic pH and in the absence of glucose, only a small fraction of the MPBA units are ionized.…”
Section: Stimuli Responsive Hydrogelsmentioning
confidence: 99%
“…Of more concern is the fact that pH in the blood can vary, especially during diabetes. Since the mechanism described above relies on an acid-base binding step, the degree of swelling depends jointly on pH and glucose concentration [151, 156]. The latter problem can be averted, in principle, either by lowering the pKa of PBA by increasing the electron withdrawing character of the groups attached to or neighboring the phenyl ring [157-159], or by incorporating Lewis base groups such as amines into the hydrogel, which can take over the role played by:OH − ions [148, 151, 160].…”
Section: Stimuli Responsive Hydrogelsmentioning
confidence: 99%
“…Polymeric materials with specific stimuli responsive behavior are widely used for medical and biotechnological applications [1][2][3][4]. In particular, polymeric hydrogel systems have attracted great interest due to their soft and flexible consistency and their ability to absorb large amounts of water, keeping at the same time their three-dimensional stability [5,6].…”
Section: Introductionmentioning
confidence: 99%